Study of B cell epitope conserved region of the Zika virus envelope glycoprotein to develop multi-strain vaccine - Oktavia Rahayu Adianingsih, Viol Dhea Kharisma (Journal of Applied Pharmaceutical Science, 2019)
A Zika virus (ZIKV) infection causes severe clinical manifestations, both in newborn baby and adult. It was considered as the public health emergency by the World Health Organization in 2016. Until now, there is no approved drug or vaccine for the treatment or prevention of multi-strain ZIKV infection. The present work attempts to identify the B cell epitope conserved region of ZIKV envelope glycoprotein through an intensive in silico study. A total of 363 ZIKV strains was retrieved from the National Center of Biotechnology Information (NCBI) database, then aligned to obtain the conserved region of ZIKV glycoprotein. The interaction between the conserved region with Axl receptor tyrosine kinase, a ZIKV receptor on the host cell, has been evaluated through molecular docking approach. The B cell epitope was identified using the immune epitope database (IEDB) web server. This study revealed that the conserved region of ZIKV envelope glycoprotein interacts with Asp9, Glu12, Glu40, Asp177, Glu243, and Glu245 of Axl receptor. Two sequences in ZIKV envelope glycoprotein, “ISDSDSRCPTQGEALKQSDTQY” (22-mer) and “SQHSGMGETDERAKVETPNSPRAEATL” (27-mer), are identified as B cell epitopes. Further studies are necessary to confirm their possibility as the potential ZIKV multi-strain vaccine in the future.
Keywords: ZIKV, B cell epitope, multi-strain, vaccine, in silico.